2020
DOI: 10.1007/s11101-020-09720-6
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids: A complementary approach to conventional therapy of COVID-19?

Abstract: COVID-19, the highly contagious novel disease caused by SARS-CoV-2, has become a major international concern as it has spread quickly all over the globe. However, scientific knowledge and therapeutic treatment options for this new coronavirus remain limited. Although previous outbreaks of human coronaviruses (CoVs) such as SARS and MERS stimulated research, there are, to date, no antiviral therapeutics available that specifically target these kinds of viruses. Natural compounds with a great diversity of chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 117 publications
(188 reference statements)
0
86
0
4
Order By: Relevance
“…The hydroxyl group of flavonoids at 7-position looks important to bind at the binding site against 3-chymotrypsin-like protease (3CLpro), and papain-like protease (PLpro). Flavonoids as a vast reservoir of therapeutically active constituents as antiviral candidates against RNA viruses, adopted from Rasouli et al (2017) , Solnier et al (2020) , and Pillaiyar et al (2020) . …”
Section: The Underlying Mechanism Of the Antiviral Activity Of Polyphmentioning
confidence: 99%
“…The hydroxyl group of flavonoids at 7-position looks important to bind at the binding site against 3-chymotrypsin-like protease (3CLpro), and papain-like protease (PLpro). Flavonoids as a vast reservoir of therapeutically active constituents as antiviral candidates against RNA viruses, adopted from Rasouli et al (2017) , Solnier et al (2020) , and Pillaiyar et al (2020) . …”
Section: The Underlying Mechanism Of the Antiviral Activity Of Polyphmentioning
confidence: 99%
“…Interestingly, many bioactive compounds derived from plants that are known to exert some antiviral effects, have attracted researchers’ attention, with a large panel of these compounds under evaluation for SARS-CoV-2 12 , 13 . Among them, flavonoids have been revealed as the most promising antiviral agents [ 14 ] . Flavonoids are a large class of food additives that have a positive impact on health and which have been extensively evaluated against a wide range of DNA and RNA viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a Phase 2 randomized double-blind placebo-controlled study aims to explore the effectiveness of a commercial plant polyphenols supplemented with vitamin D3 in a set of 200 mild COVID-19 patients (NCT04400890). Moreover, it has been suggested that quercetin, a well-characterized antioxidant, anti-inflammatory and immunomodulatory compound would be a good option in COVID-19 therapeutics ( Solnier and Fladerer, 2020 ). Currently, there are five clinical trials evaluating the adjuvant benefits of quercetin (alone or in combination) in patients with COVID-19 ( Table 1 ) The antiviral properties of resveratrol have also been shown both in vitro and in vivo ( Marinella, 2020 ).…”
Section: Polyphenols As a Protective Approachmentioning
confidence: 99%